The macroeconomic effects of a European deposit (re-)insurance scheme - Marius Clemens; Stefan Gebauer; Tobias König (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
Recent proposals for a still missing European deposit insurance scheme (EDIS) argue in favor of a reinsurance framework. In this paper, we use a regime-switching open-economy DSGE model with bank default to assess the relative efficiency of such a scheme. We find that reinsurance by EDIS is more effective in stabilizing real activity, credit, and welfare than a national fiscal backstop. We demonstrate that risk-weighted contributions to EDIS are welfare-beneficial for depositors and discuss trade-offs policymakers face during the implementation of EDIS. We also find that macroprudential regulation and EDIS can complement each other and that EDIS can prevent bank runs under certain conditions.
Keywords: E61; F42; F45; G22; G28; 330; Banking Union; Deposit Insurance; Risk-Sharing